Global change and East Asian policy initiatives - Yusuf, Shahid, 1949-; Altaf, M. Anjum, 1950-; Nabeshima, Kaoru (Washington, D.C. : World Bank, 2004)
In recent years, East Asia has been buffeted by financial shocks, rapid shifts in the competitiveness of major exports, changes in international production networking and reconfiguration in the geographical composition of production systems. This text looks at the policy initiatives that could be implemented.
"A copublication of the World Bank and Oxford University Press."
Includes bibliographical references and index.
oif 10/10/14
Loan
Keywords: East Asia -- Economic policy; East Asia -- Foreign economic relations; International trade; International finance; Globalization -- Economic aspects